Performance of linseed (Linum usitatissimum L.) varieties to varying seed rates under utera system of cultivation in North West Himalayas: PERFORMANCE OF LINSEED VARIETIES TO VARYING SEED RATES UNDER UTERA CULTIVARS - PANKAJ CHOPRA,; D BADIYALA, (Journal of Oilseeds Research, 2015)
A field experiment was conducted to study the influence of varieties ('Bhagsu', 'Surbhi' and 'Baner') and seed rates (40, 50 and 60 kg/ha) on linseed production under utera condition at experimental farm of Oilseed Section, CSK HPKV, Palampur. Variety, 'Bhagsu' being at par with 'Baner' hasrecorded significantly higher yield attributes and seed yield of linseed (565 and 566 kg/ha, respectively). Sowing using seed rate of 60 kg/ha was proved to be significantly best for recording significantly highest plant stand, growth, yield attributes and yield of linseed (643 kg/ha). Interaction of varieties and seed rate wassignificant on seed yield and plant population. 'Bhagsu' and 'Baner' when sown with seed rate of 60 kg/ha found to be best for recording significantly higher seed yield of linseed (94.0 and 92.3%, respectively over the most inferior combination).